Evaluation of five interleukin genes for association with end-stage renal disease in white Europeans. - Buckham, T; McKnight, A; Benevente, D; Courtney, A; Patterson, C; Simmonds, M; Gough, S; Middleton, D; Borrows, R; Maxwell, A (2010)
BACKGROUND: Genetic variation within interleukin genes has been reported to be associated with end-stage renal disease (ESRD). These findings have not been consistently replicated. No study has yet reported the comprehensive investigation of IL1A, IL1B, IL1RN,IL6 and IL10 genes. METHODS: 664 kidney transplant recipients (cases) and 577 kidney donors (controls) were genotyped to establish if common variants in interleukin genes are associated with ESRD. Single nucleotide polymorphism (SNP) genotype data for each gene were downloaded for a northern and western European population from the International HapMap Project. Haploview was used to visualize linkage disequilibrium and select tag SNPs. Thirty SNPs were genotyped using MassARRAY iPLEX Gold technology and data were analyzed using the chi(2) test for trend. Independent replication was conducted in 1,269 individuals with similar phenotypic characteristics. RESULTS: Investigating all common variants in IL1A, IL1B, IL1RN,IL6 and IL10 genes revealed a statistically significant association (rs452204 p(empirical) = 0.02) with one IL1RN variant and ESRD. This IL1RN SNP tags three other variants, none of which have previously been reported to be associated with renal disease. Independent replication in a separate transplant population of comparable size did not confirm the original observation. CONCLUSIONS: Common variants in these five candidate interleukin genes are not major risk factors for ESRD in white Europeans.